Effect of characteristics of the board of directors in the financial performance in insurance companies (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The aim of the research is to study the relationship between characteristics of the board of directors and the financial performance of companies. Especially the insurance companies operating in the Damascus Stock Exchange, and for that, the researcher collected data on the independent variable represented in the formation a board of directors from the governance reports published on the website of the Syrian Securities and Financial Markets Authority, as well as data on the dependent variable represented in financial performance through special financial statements and reports for insurance companies listed on the Damascus Securities Exchange and the Syrian Securities and Markets Authority, which are 7 companies, during the period from 2011 to 2016, the data was studied through the Eviews10 program.The study reached a set of results, the most important of which are:There is a negative relationship between the variables of the number of board meetings annually and independence of the board of directors and dual role to president of the board of directors with the rate of return on assets, and this relationship is not statistically significant, and there is a positive relationship between the variable of the size of the board of directors with the rate of return on assets in insurance companies, but it is not statistically significant.